Evidence that the cysteine-rich domain of Drosophila Frizzled family receptors is dispensable for transducing Wingless - Chen, Chiann-mun (National Academy of Sciences, 2004)
Members of the Frizzled family of serpentine transmembrane receptors are required to transduce Wingless/Int (Wnt) signals and contain in their N-terminal regions a conserved Wnt-binding cysteine-rich domain (CRD). Each CRD has specific affinities for particular Wnts, and it is generally believed that signal transduction depends on the strength of this interaction. Here, we report in vivo evidence that the CRD is dispensable for Frizzled family receptors to transduce Wingless (Wg), the primary Wnt signal in Drosophila. Thus, we infer that signal transduction does not require binding of Wg to the CRD, but instead depends on interactions between Wg and other portions of the receptor, or other proteins of the receptor complex.